(3GdGUdGM GdGbJUGOj aj GdOhd GdYQHjg Hjf SYQ GdUQa hGdehGRfg GdYGeg (B:s (3OQGSg fXQjg hJWHjbjg Ydi GdOhd GdYQHjg NGUI Ohd GdNdjL (B/s - (3MeOj, YHO GdYXjes ((3GdbGgQI(B: s (3OGQ GdRgQGA GdTQhb(B, s, 1998)
: (3GdebOeI (B: (3GdaUd GdChd (B: (3SjGSI SYQ GdUQa (B: (3eaghegG hCHYGOgG (B: (3GdeHMK GdChd (B: (3YdGbI UfOhb GdfbO GdOhdj HCSYGQ GdUQa (B: (3GdeHMK GdKGfj (B: (3eaghe hfXQjGJ SYQ GdUQa (B: (3GdeHMK GdKGdK (B: (3SYQ GdUQa aj Xd GdQbGHI Ydi GdfbO hGJaGbjGJ GdJLGQI hGdOaY (B: (3GdaUd GdKGfj (B: (3GdehGRfI GdYGeI hOhQgG aj GdJNWjW (B: (3GdeHMK GdChd (B: (3eaghe GdehGRfI GdYGeI (B: (3GdeHMK GdKGfj (B: (3cjajI EYOGO GdehGRfI GdYGeI hGYJeGOgG (B: (3GdeHMK GdKGdK (B: (3OhQ GdehGRfI GdYGeI aj JNWjW GdJfejI GdGbJUGOjI hGdGLJeGYjI (B: (3GdaUd GdKGdK (B: (3HQGeL GdEUdGM GdGbJUGOj aj GdhWf GdYQHj (B: (3GdeHMK GdChd (B: (3GdEUdGM GdGbJUGOj aj GdOhd GdYQHjI GdNdjLjI (B: (3GdeHMK GdKGfj (B: (3HQGeL GdEUdGM GdGbJUGOj aj GdOhd GdYQHjI eJhSWI GdONd (B: (3GdeHMK GdKGdK (B: (3HQGeL GdEUdGM GdGbJUGOj aj GdOhd GdYQHjI efNaVI GdONd (B: (3GdaUd GdQGHY (B: (3SjGSI SYQ GdUQa GdeWHbI aj GdOhd (B: (3GdeHMK GdChd (B: (3OhQ SjGSI SYQ GdUQa aj GdEUdGM GdGbJUGOj aj eUQ (B: (3GdeHMK GdKGfj (B: (3OhQ SjGSI SYQ GdUQa aj GdEUdGM GdGbJUGOj aj ShQjG (B: (3GdeHMK GdKGdK (B: (3OhQ SjGSI SYQ GdUQa aj GdEUdGM GdGbJUGOj aj GdCQOf (B: (3GdaUd GdNGeS (B: (3GdJZjQGJ GdYGdejI aj CSYGQ GdUQa hBKGQgG Ydi eUGOQ Jehjd YLR GdehGRfI GdYGeI (B((3GdMGdI GdeUQjI(B) : (3fXGe SYQ GdUQa aj eUQ (B: (3GdeHMK GdKGfj (B: (3GdJZjQGJ GdYGdejI aj CSYGQ GdUQa NdGd GdKeGfjfGJ(B.s
Keywords: (3GUdGM GbJUGOjs; (3GdHdGO GdYQHjgs; (3SYQ GdUQas; (3SjGSg GbJUGOjgs; (3eSCdg GdYedg GdHdGO GdYQHjgs; (3ehGRfI YGeIs